Foreign language education in Nigeria and the development of entrepreneurial skills among learners (2017)
Foreign language education has not been given a pride of place in Nigeria due to poor policy implementation and negative attitude towards the teaching and learning of the languages. The rate of unemployment experienced by graduates of foreign languages has reached an alarming level and this has generated a concern among stakeholders in the field of foreign languages in Nigeria. Graduates of foreign languages are not expected to be redundant, jobless or unemployed or rely entirely on teaching jobs to survive as some people in some quarters frequently claim. Stakeholders in foreign language education have failed to take critical look at the curriculum content of the various foreign languages on the curriculum to. see whether they are relevant to the socio - economic realities and values in Nigeria. This paper however seeks to examine the curriculum content of the foreign languages on the curriculum with the view to ascertaining their relevance to the socio economic realities and values in Nigeria. It was affirmed that the content of the foreign language curriculum should be able to meet the vocational and entrepreneurial needs of the teeming unemployed youths in Nigeria. There is urgent need to disabuse the mind of people on the erroneous belief that the only career available for graduates of foreign languages is teaching career. We therefore recommended that government should focus more attention on the teaching of foreign languages for specific, technical and vocational purposes in order to resolve the problem of unemployment ravaging Nigeria as a country and African continent in its entirety.